Differential gene expression Analyses in HBE/BETA thalassaemia patients and their relationship to disease severity - Alsaleh, Heba A. A. (2022)
Haemoglobin E-beta thalassaemia (Hb E/β-thalassaemia) is a common inherited genetic disorder. It is responsible for approximately half of all severe betathalassaemia cases globally. In the state of Kelantan, 50.93% of thalassaemic patients have Hb E/β-thalassaemia, and most of the cases are commonly seen in Malay compared to Chinese and Indian. Clinical heterogeneity is the most outstanding criteria among these patients ranging from mild to severe clinical courses that need a regular blood transfusion. There are many modifiers found to affect the disease presentation. However, the exact reasons behind this heterogeneity are not fully understood. This research aimed to study the differential gene expression and their possible role in the disease presentation and complications development in both transfusion-dependent (TDT) and non-transfusion dependent (NTDT) HbE/β-thalassaemia patients. It was conducted with the aid of RT2 profiler PCR array and microarray that were used in gene expressional study in reticulocytes and erythroid progenitors, respectively. Three normal controls and a total of 20 patients were enrolled in this study; 10 (50%) were TDT, and 10 (50%) NTDT. The reticulocytes study showed the up-regulation of BAX and BAD genes in TDT patients, which have a role in apoptosis induction through the mitochondrial apoptotic pathway. Their up-regulation in TDT may play a role in the reticulocytes’ apoptosis, mature RBCs' short life span and eryptosis. Flow cytometry study showed higher apoptosis in the erythroid progenitors of TDT patients. The increased apoptosis in erythroid progenitors and the up-regulation of BAD and BAX of reticulocytes in TDT may be linked to the down-regulation of the genes involved in the PI3k/AKT pathway in the same patients’ group genes. Pathway and ontology analysis showed the involvement of osteoporosis and bone regulating factors related to the VDR pathway and the negative regulation of osteoclast differentiation in the TDT group. The genes involved can be therapeutic targets like SPP1 and MAFB. Their activation act to reduce the disease burden by reducing anaemia and alleviating bone marrow complications. In summary, our study showed the expression of interesting genes and pathways that may potentially modify the disease presentation and the development of the complications.